2023
DOI: 10.1002/acn3.51957
|View full text |Cite
|
Sign up to set email alerts
|

Impact of early cognitive impairment on outcome trajectory in patients with intracerebral hemorrhage

Zuo‐Qiao Li,
Xiao‐Qing Bu,
Jing Cheng
et al.

Abstract: ObjectiveTo assess the prevalence and factors associated with early cognitive impairment in intracerebral hemorrhage (ICH) patients and to describe short‐term recovery trajectories among ICH patients with early cognitive impairment.MethodsWe prospectively enrolled ICH patients without baseline dementia in our institutions. Cognitive function was assessed using mini‐mental state examination (MMSE), and functional outcome was evaluated at discharge, 3, and 6 months after symptoms onset using the modified Rankin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…With posterior circulation structures, a study found significant cognitive impairment in patients with cerebellar infarcts; specifically a higher incidence of significant impairment with right cerebellar lesions showing significantly impaired executive function ( Liu et al, 2022 ). Similar correlations in intracerebral hemorrhage location and resultant cognitive impairment post-stroke were observed in a prospective study that found a strong correlation where patients with lobar hematoma were 4.58 times more likely than patients with non-lobar ICH ( Li et al, 2023 ). Further correlation localizing areas where cognitive impairment is significant would potentially be beneficial for making post-stroke care more individualized.…”
Section: Stroke Territorysupporting
confidence: 74%
See 1 more Smart Citation
“…With posterior circulation structures, a study found significant cognitive impairment in patients with cerebellar infarcts; specifically a higher incidence of significant impairment with right cerebellar lesions showing significantly impaired executive function ( Liu et al, 2022 ). Similar correlations in intracerebral hemorrhage location and resultant cognitive impairment post-stroke were observed in a prospective study that found a strong correlation where patients with lobar hematoma were 4.58 times more likely than patients with non-lobar ICH ( Li et al, 2023 ). Further correlation localizing areas where cognitive impairment is significant would potentially be beneficial for making post-stroke care more individualized.…”
Section: Stroke Territorysupporting
confidence: 74%
“…A retrospective study that enrolled 184 ICH patients showed as high as 84% of patients developed cognitive decline after hemorrhage ( Banerjee et al, 2018 ). Another recent prospective study published in 2023 identified early cognitive impairment as prevalent among ICH patients and significantly decelerated the recovery of functional outcomes in patients ( Li et al, 2023 ). As a result, in ICH patients, conducting early cognitive assessments will also be crucial in formulating personalized predictions, targeted interventions, and rehabilitation strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Should these models perform sub-optimally on certain tasks, the efficacy of our methodology could be compromised. Lastly, our model integrated CT imaging data and text, which has been demonstrated to influence prognosis classification outcomes, such as gender [ 27 , 28 , 29 ], early cognitive status [ 30 ], and the location and volume of the hemorrhage [ 31 , 32 ]. Therefore, any loss of information between modalities might impair the model’s performance.…”
Section: Discussionmentioning
confidence: 99%